Penguatan Kompetensi Transformasi Digital Mahasiswa Universitas Battuta melalui Workshop Pemanfaatan Teknologi Cloud Computing - Ginting, Subhan Hafiz Nanda; Wahyuni, Dewi; Sridewi, Nurmala; Wayahdi, M. Rhifky; Darma, Surya (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Digital transformation is a strategic necessity in facing the dynamics of the world of work and developments in the information technology industry. Students, as future professionals, are required to have relevant digital competencies, particularly in the use of cloud computing technology, which is increasingly being used in data management, application development, and network-based collaboration. This community service activity aims to strengthen the digital transformation competencies of Battuta University students through the implementation of structured and applicable cloud computing technology utilization workshops. The methods used in this activity include participant needs analysis, material preparation, interactive workshop implementation, practical guidance, and activity outcome evaluation. The workshop material covered an introduction to the basic concepts of cloud computing, an understanding of key cloud services, and practical use of cloud platforms for data storage, access management, and implementation of simple services. Evaluation was conducted through pre-tests, post-tests, and observation of participant engagement during the activity. The results of the activity showed an increase in students' conceptual understanding and technical abilities in utilizing cloud technology. This activity contributed positively to improving students' readiness to meet competency demands in the digital era and strengthening their technological literacy and adaptation.